Masculinity in the Midst of Mindfulness: Exploring the Gendered Experiences of At-risk Adolescent Boys. (April 2020) - Lomas, Tim; Garraway, Ellie; Stanton, Chloe; Ivtzan, Itai
Teenage boys are a source of considerable concern in society, with generally poorer health, educational, and social outcomes than their female counterparts. Of particular concern are "at-risk" adolescents, who by definition are liable to poorer outcomes than peers not deemed at-risk. However, there are indications that activities such as mindfulness may offer opportunities for such adolescents to negotiate more positive constructions of masculinity. This study piloted a new four-week mindfulness-based intervention, created specifically for a group of eight at-risk adolescent boys at a school in London. In-depth, semi-structured qualitative interviews were conducted with participants before and after the intervention and analyzed using grounded theory. The data revealed an overarching theme of "pressure control." Participants depicted themselves as facing multiple pressures, many of which related to making the difficult transition from childhood to adulthood. However, the context of the intervention enabled them to generate a masculine construction in which they were able to reclaim agency and self-control. Notably, such control was often exercised in the direction of facilitating emotional connection and agility, thus subverting traditional masculine expectations. The results show that at-risk adolescent boys are capable of more nuanced and skilled emotional competencies than they are often given credit for.